Developing microsatellite markers for Galearis rotundifolia (the roundleaf orchid) - Sairuv, Farista (My University, 2025)
There is a human-caused global biodiversity crisis imperiling both the natural and human world. Plant species are particularly vulnerable. Genetic diversity is important to species’ health and survival, so genetic tools should be developed to assess it. Microsatellite markers, which are regions of DNA where a few base pairs repeat in a pattern, are a one such tool. Galearis rotundifolia is an orchid species found throughout northern North America, and this project aims at developing microsatellite markers for this species. Leaf samples were collected from the Wagner Natural Area, and their DNA was extracted, fragmented, and amplified according to the FIASCO method. Fragments likely to contain microsatellites were pulled down using FIASCO, and next generation sequencing was done to find microsatellites. Primer 3 was used to find primers for the longest dinucleotide repeat microsatellites, and these primers were tested in the same PCR conditions, with an annealin g temperature of 56oC. 13 primer pairs were successful at amplifying G. rotundifolia DNA. 3 Primer PCR was done with the DNA of 3 individuals, amplifying 11 of the microsatellites that had been successfully amplified in the first round of PCR. This DNA was sent for fragment analysis to test which of the microstatellites were polymorphic. 5 microsatellites showed evidence of being polymorphic. The primer pairs developed for these 5 microsatellites, as well as primer pairs developed by future students, can be used to assess genetic diversity and other parameters, and inform and guide conservation.
Keywords: microsatellite markers; Galearis rotundifolia; roundleaf orchid